ANALISIS STRATEGI LOGISTIK PERUSAHAAN DENGAN MENGGUNAKAN ANALYTICAL NETWORK PROCESS (ANP) - Nurhadi Siswanto; Stefanus Eko Wiratno; Andi Irma Arianty (Jurnal Teknobisnis, 2005)
Fierce competition in today's global market has forced industrial players to think how to win the competition. Application of logistics and supply chain management strateg is one way to win the competition. Logistics and supply chain management is influenced by external and internal factors. The external factors are corporate strateu alliance, technology development, fierce competition environment, while internal factors are decision support system, information system integration, logistics system, and targeted improving performance. This research tries to evaluate logistics strategy alternatives using Analytical Network Process (ANP). ANP uses feedback approach to evaluate dynamic multi direction relationship between decision attributes. Because external factors influence the process of strategic decision making, ANP approach is used to get the best logistics and supply chain strategy for current situation.